1975
DOI: 10.1128/jb.124.1.542-549.1975
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleic acid polymerase of germinating Bacillus cereus T

Abstract: It appears that a de novo synthesis of the deoxyribonucleic acid-dependent ribonucleic acid-polymerase in Bacillus cereus T takes place fairly late in outgrowth, at the onset of the vegetative cycle. Therefore, the ribonucleic acid-polymerase used by germinating spores is the one carried on from sporulating cells. However, the sporal enzyme is less soluble that the vegetative one, and its "core" is bound to two extra peptides. This complexing to other molecules could play a role in the regulation of gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1975
1975
1991
1991

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…It has been suggested that the enzyme can no longer recognize sporulation promoter sites because of a lack of interaction with sporulation-associated proteins equivalent to the vegetative ac factor (109,185). Many reports have indicated the presence of more than one type of RNA polymerase in sporulating cells (38,63,96,126,163,185,218), and this is consistent with the idea that polymerase structural changes, or changes of associated protein factors, play a role in controlling the transcription of spore genes. The presence of more than one RNA polymerase is not surprising, since it is clear that sporulating cells continue to make vegetative mRNA (2,64,66,292,328).…”
Section: Mutations To Antibiotic Resistance That Alsosupporting
confidence: 76%
“…It has been suggested that the enzyme can no longer recognize sporulation promoter sites because of a lack of interaction with sporulation-associated proteins equivalent to the vegetative ac factor (109,185). Many reports have indicated the presence of more than one type of RNA polymerase in sporulating cells (38,63,96,126,163,185,218), and this is consistent with the idea that polymerase structural changes, or changes of associated protein factors, play a role in controlling the transcription of spore genes. The presence of more than one RNA polymerase is not surprising, since it is clear that sporulating cells continue to make vegetative mRNA (2,64,66,292,328).…”
Section: Mutations To Antibiotic Resistance That Alsosupporting
confidence: 76%
“…We next tried to characterize protein I and protein 11, which are synthesized in the presence of ActD during germination of B. subtilis. To approach this problem, we attempted to examine their relationship to ribosomal proteins and Rpase, since these proteins play important roles in gene regulation and may plausibly be activated during germination so that the dormant spores can participate in active outgrowth and the subsequent vegetative growth ( KOBAYASHI 1972, COHEN et al 1972, HATTORI et al 1975. Such proteins may be expected to be synthesized de novo during early germination.…”
Section: Resultsmentioning
confidence: 99%